Իրանի նկատմամբ Միացյալ Նահանգների քաղաքականությունը Մեհդի Բազարգանի կառավարման շրջանում - Ստամբոլցյան, Անուշ («Զանգակ - 97»)
After the departure of Shah Mohammed Reza Pehlevi in January 16, 1979, due to the absolutely new Situation in Iran, the main concern of the U SA became to keep its fbrmer positions and influence here. The author studies the circumstances of the process of the development of the USA policy towards Iran during the rulership of Mehdi Bazargan, peculiarities of its forms and methods, as well as those important factors which, in spite of continuous efforts of the USA, finally led to the failure of this policy.
Keywords: Պատմություն; Քաղաքականություն; Միջազգային հարաբերություններ